Indeks Glisemik Kacang Buncis (Phaseolus vulgaris) dan Kacang Panjang (Vigna sesquipedalis) serta Uji Efek Hipoglisemiknya pada Tikus Sprague Dawley - Marsono, Y.; Triwitono, Priyanto; Kanoni, Sri (Universitas Atma Jaya Yogyakarta, 2005)
Glycemic index (GI) of foods has been suggested as an additional parameter in selecting foods for the diabetic patients in nutritional management. GI was measured as the area under the postprandial blood glucose curve for a food expressed as a percentage of the area after the consumption of reference food (bread). In this research two legumes were investigated including snap bean (Phaseolus vulgaris L.) and yardlong bean (Vigna sesquipedalis). The objectives of this research were (i) to determine the IG of the beans and (ii) to investigate the effects of these legumes on serum glucose concentration of alloxan-induced diabetic rats. Ten health and normal volunteers (not diabetic) were provided. The volunteers took an overnight fasting, blood were drawn in the morning and analyzed for serum glucose. Then they were given the test beans containing total carbohydrates equivalent to 25-g glucose to be consumed. Blood samples were drawn for glucose measurement every 30 minutes until 120 min after meal. Serum glucose was determined enzymatically and the glucose responses were drawn graphically to calculate the GI of the beans. These beans were evaluated for their hypoglycemic properties in alloxan-induced diabetic rats. They were fed modified AIN 93 diets contain 20% of energy derived from snap bean or yardlong bean for 28 days. Serum glucose concentrations were measured weekly. It was found that with white bread as the food standard the GI of the snap bean and yard long bean were 43 and 86, respectively. In 28 days of diet intervention, snap bean decreased the serum glucose level by 73% (from 212mg/dL to 56mg/dL). Similar effect were found for the yardlong bean. This bean can reduced serum glucose level about 73% (from 224mg/dL top 61mg/dL), but both were similar to control diet that decreased the serum glucose level about 72% .